MENINGKATKAN KUALITAS HASIL BELAJAR IPA MELALUI ALTERNATIF MODEL PEMBELAJARAN - Alvi Rosyidi; Marjono Marjono (PAEDAGOGIA, 2008)
The purpose of this research is to know the influence of certain teaching method in increasing the quality of the students' achievement of open SLTP viewed from the kind of tests. Besides, it is directed to get the most effective teaching method which can be applied as the positive alternative in increasing the quality of the SLTP student' achievement. The kind of research used is an experimental comparative research using two ways Anava. Here statistical formulas were three levels comparative from one variable namely teaching method with module; teaching method with video-cassette (electronic media); and teaching method with problem solving approach, and their influence to the tied variable based on other factor whether the test is objective or essay. The result of the research shows that teaching method with electronic media is the most appropriate to increase the quality of studying biology; the second was teaching by module completed with creative problems solving, and the last was teaching method with module. Besides, it revealed that subjective test model is better than objective test. There was no interaction between certain teaching methods with the kind of the test.